The Economic Value of Cultural Diversity: Evidence from US Cities - Gianmarco I.P. Ottaviano; Giovanni Peri (Fondazione Eni Enrico Mattei (FEEM), 2004)
We use data on wages and rents in different U.S. cities to assess the amenity effects on production and consumption of cultural diversity as measured by diversity of countries of birth of city residents. We show that US-born citizens living in metropolitan areas where the share of foreign-born increased between 1970 and 1990 have experienced a significant average increase in their wage and in the rental price of their housing. Such finding is economically significant and robust to omitted variable bias and endogeneity bias. We then present a model in which cultural diversity may have both production and consumption amenity or disamenity effects. As people and firms are mobile across cities in the long run, the model implies that the joint results from the wage and rent regressions are consistent with a dominant production amenity effect of cultural diversity.
Keywords: O4; R0; F1; 330; Cultural diversity; Productivity; Local amenities; Urban economics; Interkulturelle Beziehungen; Wohnstandort; Stadtquartier; Lohn; Miete; Bevölkerungsstruktur; Nutzen; Schätzung; USA